2022
DOI: 10.2196/28379
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience and Satisfaction in Online Reviews of Obstetric Care: Observational Study

Abstract: Background The quality of care in labor and delivery is traditionally measured through the Hospital Consumer Assessment of Healthcare Providers and Systems but less is known about the experiences of care reported by patients and caregivers on online sites that are more easily accessed by the public. Objective The aim of this study was to generate insight into the labor and delivery experience using hospital reviews on Yelp. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…We obtained reviews for a total of 38 apps, with 25 apps from the Google Play Store and 13 apps from the Apple Play Store. Consistent with prior works studying user reviews on online platforms [16][17][18], the distribution of ratings follows a bimodal distribution as shown in S1 Fig. ~78% of the reviews are either 1 star or 5 stars.…”
Section: Resultssupporting
confidence: 84%
“…We obtained reviews for a total of 38 apps, with 25 apps from the Google Play Store and 13 apps from the Apple Play Store. Consistent with prior works studying user reviews on online platforms [16][17][18], the distribution of ratings follows a bimodal distribution as shown in S1 Fig. ~78% of the reviews are either 1 star or 5 stars.…”
Section: Resultssupporting
confidence: 84%
“…We have already mentioned various issues on the COVID-19 vaccine perception and hesitancy [7,20,33,66]. Other observations on patients are also important, such as classification of self-harm behaviors in EHRs [94], analysis of unnoticed and unresolved safety incidents in patients [95], analysis of web-based reviews of sanctioned physicians [96], and patient experience and satisfaction in online reviews [97].…”
Section: Patients As Actors Of the Healthcare Processmentioning
confidence: 99%
“…For example, Quinones et al [31] also found that discussions of pain management were present in both positive and negative WPRs of neurosurgeons; top-rated WPRs demonstrated the importance of compassion for levels of patient satisfaction. The study by Seltzer et al [32] on patient experiences in web-based reviews of obstetric care revealed that narratives found in WPRs related to obstetrics provide meaningful information toward the improvement of obstetric care experiences.…”
Section: Theoretical Implicationsmentioning
confidence: 99%